2016
DOI: 10.5455/bcp.20151205113132
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Turkish PTSD-Short Scale in a Sample of Undergraduate Students

Abstract: ABSTRACT:Psychometric properties of the Turkish PTSD-Short Scale in a sample of undergraduate students Objective: The National Stressful Events Survey for Posttraumatic Stress Disorder (PTSD)-Short Scale (NSESSS-PTSD) allows dimensional self-rating assessment of PTSD according to the DSM-5. The aim of the present study was to evaluate psychometric properties of this scale as Turkish PTSD-Short Scale (PTSD-SS) in a sample of undergraduate students in Turkey.Method: Participants included 415 university students,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…A clinical cut-off score was also calculated based on the score 24 (LeBeau et al 2014). A student-based study found the Turkish version of the NSESSS-PTSD to be psychometrically sound PTSD screening measure with high convergent and discriminant validity, and reliability as well as good sensitivity and specificity (Evren et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…A clinical cut-off score was also calculated based on the score 24 (LeBeau et al 2014). A student-based study found the Turkish version of the NSESSS-PTSD to be psychometrically sound PTSD screening measure with high convergent and discriminant validity, and reliability as well as good sensitivity and specificity (Evren et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Scoring rules were based on DSM-IV or DSM-5 (APA, 1994(APA, , 2013. Prevalence rates of PTSS were obtained via the Davidson Trauma Scale (DTS, Davidson et al, 1997), IES (Horowitz et al, 1979 (in one study in combination with items from the General Health Questionnaire [GHQ, Goldberg, 1988]), IES-R (Weiss & Marmar, 1997) , 2000), Turkish PTSD-Short Scale (Evren et al, 2016), and Trauma Screening Questionnaire (TSQ, Brewin et al, 2002). There was a mixture of applied scoring rules as well as cutoff scores to determine clinically relevant symptom levels, in some cases varying for the same instrument (e.g., IES and IES-R).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The internal consistency coefficient of PTSD-SS was 0.91 (Evren et al, 2015). In this study, the internal consistency value was found to be 0.80.…”
Section: Post-traumatic Stress Disorder-short Scale (Ptsd-ss)mentioning
confidence: 49%
“…The scale developed by LeBeau et al ( 2014) was adapted into Turkish by Evren C et al (2015), and its validity and reliability were established (Evren et al, 2015;LeBeau et al, 2014). The scale consists of 9 items.…”
Section: Post-traumatic Stress Disorder-short Scale (Ptsd-ss)mentioning
confidence: 99%